História e memória: o mobral em Porto Nacional (1970) - Mousinho, Tainara Ferreira (Universidade Federal do Tocantins, 2022)
The Movimento Brasileiro de Alfabetização [Brazilian Literacy Movement] – MOBRAL was inserted in the context of the military regime promising to significantly reduce the illiteracy rate in Brazil. This article has as its theme the study of the MOBRAL program in Porto Nacional, located in the old northern region of Goiás, in the 1970s, with the objective of understanding its development. For this,se used the methodology of bibliographic and documentary research in relation to MOBRAL, mediated by the perspective of oral history. The research showed a series of difficulties for the development of MOBRAL in Porto Nacional, such as the devaluation of the Movement by the municipal government and, consequently, the lack of financial and material resources for its implementation. On the other hand, there is a positive memory in relation to the meaning of MOBRALfor the professionals and students involved in the referred period of its operation.